A library of routines for incoherent scatter radar data processing - Bogomaz, O. V.; Kotov, D. V. (НТУ "ХПІ", 2014)
The structure of the developed dynamic link library of routines for incoherent scatter radar data processing and incoherently scattered signals simulation and the examples of its application are described.

У статті описано структуру розробленої динамічної бібліотеки процедур для обробки даних радара некогерентного розсіяння та імітації некогерентно розсіяних сигналів, а також приведено приклади її використання.
Keywords: incoherent scatter; data processing; simulation; numerical computing routines; некогерентне розсіяння; обробка даних; моделювання; чисельні обчислювальні процедури